211k views
5 votes
If f (x) = x over 2 - 2 and g(x) = 2x squared + x - 3, find (f + g) (x)

User Modkzs
by
5.5k points

1 Answer

3 votes


f(x) = (x)/(2) - 2 \\


g(x) = 2x + {(x - 3})^(2)


f(x) + g(x) = (f + g)(x)


( (x)/(2) - 2) +( 2x + ({x - 3})^(2) \: ) = \\


(x)/(2) - 2 + 2x + {x}^(2) - 6x + 9 = \\


{x}^(2) - 6x + 2x + (x)/(2) + 9 - 2 = \\


{x}^(2) - 4x + (x)/(2) + 7 = \\


{x}^(2) - (8)/(2)x - (1)/(2)x + 7 = \\


(f + g)(x) = {x}^(2) - (9)/(2)x + 7 \\

_________________________________

Done....

♥️♥️♥️♥️♥️

User Adamsfamily
by
5.5k points